Economic efficiency of the Mexican metropolitan regions between 1998 and 2008 - Alejandra Trejo (European Regional Science Association (ERSA), 2012)
Nowadays metropolitan spaces are key territorial references for analysis and action. They are of critical economic, social and political importance. Three decades ago the Mexican urban structure was characterized by the existence of a principal city, Mexico City, where the national government, the largest concentration of population, industry, services and infrastructure seats. However the urban system has become more complex. The restructuring has taken the form of the emergence of several cities with qualities of metropolitan areas. These metropolitan agglomerations concentrate more than 70% of the productive capacity and therefore the largest part of the economic growth is expected to originate in the metropolises. This creates challenges for these regions, such as the need of jobs and capital accumulation but it also offer the best opportunity to expand economically and improve the quality of life for the population. Yet, productivity, profits and efficiency are distributed heterogeneously among metropolitan areas. The most mobile factors of production, capital and technological knowledge, are dominated by a few urban centers, thus other cities are left with obsolete physical capital and the less qualified laborers. Presently, the country faces the challenge to extend the urban development benefits to all cities and inhabitants. The need of competitive and efficient metropolis is relevant to this aim. A profound knowledge and diagnosis about the specificities and differences among metropolis is called for. However there has been a relatively scarce recording of productivity and efficiency in cities and metropolitan areas in Mexico. This paper attempts to add evidence on the issue of disparities in efficiency levels among the metropolitan economies in the period 1998-2008 by examining the differences and evolution of technical efficiency. I analyze the technical efficiency of the 56 metropolitan regions in Mexico by means of data envelopment analysis using economic censuses data for 1998, 2003 and 2008. In the paper I will resent information to characterize, delimit and classify functionally the metropolitan zones in order to guide further analysis as well as competitiveness projects and programs that support their performance and participation in the global and local scenes.
Keywords: 330; Technical efficiency; productivity; competitiveness; Metropolitan regions; Mexico